Um apagador quântico com estados de Bell - Stephen Patrick Walborn (2000)
In this dissertation, an optical quantum eraser experiment, which can be considered an optical analogy of an experiment proposed by Scully, Englert and Walther(SEW) [1] is performed. Using photons in entangled Bell-states, we can choose whether to observe which-path information or an interference pattern. An appealing feature of this quantum eraser is that the experiement actually uses a Young double-slit to create interference. One photon of an entangled pair is incident on a Youngdouble slit of appropriate dimensions to create an interference pattern on a distant \screen". Quarter-wave plates, orientated so that their fast axes are orthogonal, are placed in front of each slit, serve as which-path markers. The presence of the quarter-wave plates destroys the interference pattern. To recover interference, an appropriate polarization measurement on the other entangled photon is performed. In addition, a \delayed quantum erasure" experiment is performed. The dangers of an erroneous interpretation of quantum theory in the delayed erasure situation are briey discussed. The generation of polarization-entangled photons using spontaneous parametric down-conversion is briey studied. It is shown that, through type-II non-colinear phase matching, the non-linear BBO (_-BaB2O4) cristal creates highly-entangled photons. Curves of polarization interference are obtained, proportional to sin(_A _ _B), with visibilities greater than 0:95.